Theorizing About an AOM President's Response to Crisis and the Counter Responses It Evoked. (July 2019) - Bartunek, Jean M.; Elsbach, Kimberly D.; Bell, Emma; Markides, Costas; Christianson, Marlys G.; Sutcliffe, Kathleen M.; Pratt, Michael G.; Coyle-Shapiro, Jacqueline A.-M.; Glynn, Mary Ann; Ocasio, William; Burton, M. Diane; Ventresca, Marc J.
Organizational crises have often stimulated scholarly theorizing that has been productive for our field. Rarely, however, are there opportunities to theorize regarding crises that happen in our own professional associations. A crisis experienced by Professor Anita McGahan when she was the President of the Academy of Management, described in an accompanying article, has presented such an opportunity. In this set of nine brief reflections, several scholars have considered how McGahan's actions with regard to that crisis can be understood conceptually and how they may stimulate development of previously established conceptual perspectives. These reflections make evident that McGahan's actions cannot be appreciated without recognition of the complex dilemmas to which she was responding. These dilemmas include issues of trustworthy leadership, gendered power, leader voice, sensemaking and learning, organizational identities, psychological contracts, institutional leadership, and "good bureaucracy."